Makna Teologis Frasa “Waktunya Sudah Dekat” Dalam Wahyu 22:10 Dan Implikasinya - Wesley, Jhon; Yakob, Yakob (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2023)
The phrase “the time is near” is one of the passages that has become familiar among Christians in understanding the second coming of Christ to earth. However, there are many Christians who do not understand the theological meaning of this word precisely. No wonder the coming of Christ becomes meaningless for some believers. Some think it's just a fictional story. However, some people try to interpret the coming of the Lord Jesus with calendar dates. Actually, what is the theological meaning and urgency of the phrase above? This article aims to discuss the meaning of the phrase "the time is near" according to the Book of Revelation 22:10. The method used is qualitative with a literature study approach. The findings show that first, the theological meaning of the phrase "The Time Is Near" states a good opportunity from God to fulfill the second coming of Christ to rule as King, defeat Satan and his army, Judgment Day, and provide deliverance from suffering for His people. Second, it refers to the event of Christ's return to this world which is unexpected (sudden) and happened quickly, and not known by anyone except the Father in Heaven. The implications of the second coming of Christ about the phrase "The time is near" are, First, every believer must have the certainty that Christ's second coming will give His people deliverance from suffering in this world. Second, the second coming of Christ cannot be known by anyone, except for the Father in Heaven. Third, believers must persevere in faith, be faithful in preaching the Gospel, and be ready at all times waiting for Christ to return and reign as King.AbstrakFrasa kata “waktunya sudah dekat” merupakan salah satu bagian yang menjadi familiar di kalangan orang Kristen dalam memahami kedatangan Kristus kedua kali ke bumi. Namun, ada banyak orang Kristen kurang memahami dengan tepat makna teologis dari kata tersebut. Tidak heran kedatangan Kristus menjadi tidak berarti bagi sebagian orang percaya. Ada yang beranggapan itu cerita fiksi belaka. Namun, ada juga orang yang mencoba menafsirkan kedatangan Tuhan Yesus dengan penanggalan kalender. Sebenarnya, apa makna teologis dan urgensi dari frasa tersebut di atas?  Artikel ini bertujuan untuk membahas makna frasa ‘waktunya sudajt dekat” sesuai Kitab Wahyu 22:10. Metode yang digunakan adalah Kualitatif dengan pendekatan studi pustaka. Hasil temuan menunjukkan bahwa pertama, makna teologis frasa “Waktunya Sudah Dekat” menyatakan kesempatan yang baik dari Allah menggenapi kedatangan Kristus kedua kali memerintah sebagai Raja, mengalahkan Iblis dan pasukannya, Hari Penghakiman, serta memberikan kelepasan dari penderitaan bagi umat-Nya.  Kedua, mengacu kepada peristiwa kedatangan Kristus kembali ke dunia ini yang tidak terduga (tiba-tiba) dan terjadi dengan cepat, serta tidak diketahui oleh siapapun, kecuali Bapa di Surga. Implikasi kedatangan  Kristus kedua dalam kaitan dengan frasa “Waktunya sudah dekat’ adalah, Pertama, setiap orang percaya harus memiliki kepastian akan kedatangan Kristus kedua kali memberikan umat-Nya kelepasan dari penderitaan di dunia ini. Kedua, kedatangan Kristus kedua kali tidak bisa diketahui siapun, kecuali Bapa di Surga. Ketiga, orang percaya harus bertekun dalam iman, setia mengabarkan Injil dan siap sedia setiap saat menantikan Kristus datang kembali dan memerintah sebagai Raja.